Morfologia e imunoistoquímica dos carcinomas de células escamosas alimentares associados ao consumo de Pteridium aquilinum em bovinos - Masuda, Eduardo Kenji (2007)
To determine the main factors influencing the biological behavior of 40 squamous cell carcinomas (SCC) of the upper digestive tract (UDT) of cattle associated with spontaneous ingestion of bracken fern (Pteridium aquilinum), morphological, including cell proliferation, and immunohistochemical aspects were studied. The aspects analyzed included anatomical localization of SCCs, degree of differentiation, occurrence and distribution of metastasis, intensity of the lymphoplasmocytic inflammatory infiltrate (LPII), of the desmoplastic reation, tumor-associated tissue eosinophilia, and the cell proliferation index evaluated through quantification of the argyrophilic nucleolar organizer regions (AgNORs). Forty two percent of SCCs were in the cranial region, 12.5% in the middle, and 45% in the caudal region of the UDT. The neoplasms were classified as well differentiated (WD-SCC; 67.5%), moderately differentiated (MD-SCC; 20%), or poorly differentiated (PD-SCC; 12.5%). When the degree of differentiation was correlated to the anatomical localization, it was observed in the cranial region that 88.2% were WD-SCC and 11.8% were MD-SCC. In the middle region, 60% were WD-SCC, 20% were MD-SCC, and 20% were PD-SCC. In the caudal region, 50% were WD-SCC, 27,8% were MD-SCC, and 22,2% were PD-SCC. Metastasis occurred in 57.75% of the cases, mostly to regional lymph nodes, and were observed in 58.82% of the cases with SCCs of the cranial region; in 40% of the middle region, and in 61.11% of the caudal region. Metastasis to regional lymph nodes and/or to distant organs were found in 44.44% of WDSCC, 75% of MD-SCC, and 100% of PD-SCC. Migration and invasion patterns were analyzed through the immunohistochemistry technique for cytokeratin. Islands and ribbons of neoplastic keratinocytes predominated in the WD-SCCs. The patterns varied greatly in the MD-SCCs, although small aggregates, ribbons, and cords predominated. PD-SCCS were characterized by small aggregates and individual cells. Lymphatic or hematogenous invasion were detected in 11/40 SCCs. There were SCCs originating from the ductal epithelium of the salivary glands. This finding was not previously reported. The intensity of the LPII was more accentuated in the BD-SCCs than in the MDs or PDs. The intensity of the desmoplastic reaction was quantified through the immunohistochemistry technique for vimentin, and was more severe in the PD-SCCs. The tumor-associated tissue eosinophilia (TATE) was measured in the SCCs and classified as mild, moderate, or severe. The only positive statistically significant association was established between TATE and LPII intensities. Cell proliferation was evaluated through quantification of the argyrophilic nucleolar organizer regions (AgNORs) on the neoplastic keratinocytes. AgNOR mean value and standard deviation (±sd) for WD-SCCs were 1.65 (±0.23), for MD-SCCs were 1.88 (±0.31), and for PD-SCCs were 2.39 (±0.26). The correlation between the AgNOR index and each histopathological grade was statistically significant. In conclusion, the factors which influenced the biological behavior of SCCs were the degree of cell differentiation, the patterns of migration and invasion, the intensity of LPII, TATE and desmoplastic reation, and the cell proliferation index measured through quantification of the AgNORs.